Floral biology and pistil receptivity of the drumstick tree (Moringa oleifera Lam.) - Zhang, Junjie; Lin, Mengfei; Chen, Hanbin; Zhu, Qin; linh, Vu Ngoc; Chen, Xiaoyang (Archives of Biological Sciences, 2018)
Drumstick (Moringa oleifera Lam.) has a wide range of uses due to its high nutritional value and the high oil content of its seeds. Many aspects of its reproductive biology remain poorly understood. We investigated the floral morphology of drumstick, its stigma receptivity and the structural and cytochemical features of the stigma and style at different developmental stages. The inflorescences are panicles of hermaphroditic flowers, with a pistil consisting of one open-type stigma and a hollow stylar canal. Stigma receptivity was assayed based on pollen germination, pollen tube growth and fruit set following artificial pollination. Flowers at later developmental stages exhibited greater stigma receptivity, higher percentages of pollen germination and a higher fruit set than those in earlier stages. Enhanced stigma receptivity was associated with increased amounts of insoluble polysaccharides, lipids and proteins in the canal cells at later developmental stages. An ultrastructural study of the cells lining the canal indicated that they were secretory cells containing an enlarged endoplasmic reticulum, dictyosomes, mitochondria, plastids and ribosomes. Post-anthesis, these organelles exhibited degeneration at the end of the secretory phase. This study provides an important contribution to current knowledge of the anatomy and ultrastructure of the style and stigma in drumstick. https://doi.org/10.2298/ABS170205046Z Received: February 5, 2017; Revised: April 10, 2017; Accepted: May 8, 2017; Published online: November 20, 2017 How to cite this article: Zhang J, Lin M, Chen H, Zhu Q, Linh VN, Chen X. Floral biology and pistil receptivity of the drumstick tree (Moringa oleifera Lam.). Arch Boil Sci. 2018;70(2):299-305.